(3GdUMGaI GdYQHjI hGdOhdjI (B:s (3Gdeaghe, GdNUGFU, GdeTGcd, GdfeGPL, GdEJLGgGJ (B/s - (3GdeTgOGfj, SYO SdeGfs ((3GdEeGQGJ GdYQHjI (B:s (3OGQ GdcJGH GdLGeYj ,s, 2014)
(3GdUMGaI GdYQHjI (B- (3GdUMGaI GdOhdjI (B- (3gjFGJ (B- (3efVeGJ GdUMGaI GdCeQjcjI (B- (3GdUMGaI GdHQjWGfjI (B- (3GdVMGaI GdaQfSjI UMGaI GdehGWf (B- (3UMGaI GdeOhfGJ (B- (3GdUMGaI GdESJbUGFjIs
Keywords: (3GdUMGaI GdOhdjIs; (3GdUMGaI GdYQHjIs; (3GdUMGaI GdaQfSjI s; (3UMGaI GdehGWfs